Exclusive breastfeeding rate and factors associated with infant feeding practices in Indonesia - Yovita Ananta; Ellen Gandaputra; Elina Waiman; I Gusti Ayu Nyoman Partiwi; Nanis Sacharina Marzuki; Elizabeth Yohmi; Eveline Panjaitan; Hanifah Oswari; Badriul Hegar (Indonesian Pediatric Society, 2016)
Background Breast milk is the ideal food for infants. According to the 2007 Indonesian National Household Health Survey, only 23% of mothers exclusively breastfeed for six months.Objectives To determine the rate of exclusive breastfeeding in Indonesia, to evaluate factors associated with infant feeding practices, and to compare the nutritional and developmental status between exclusively-breastfed and formula-fed infants.Methods A survey was conducted in hospitals located in 17 provinces in Indonesia. The rate of exclusive breastfeeding was calculated. Many variables were investigated as potential predictors for exclusive breastfeeding using a multivariable logistic regression analysis. Further analysis was performed to compare the nutritional and developmental status between exclusively breastfed and formula-fed infants at the time of survey.Results From 1,804 infant subjects, the overall rate of exclusive breastfeeding was 46.3%, ranging from 10.5% in East Java to 66.9% in Jambi. Predominant breastfeeding, complementary feeding, and formula feeding rates were 14.3%, 8.6%, and 30.7%, respectively. Maternal unemployment was associated with a longer duration of breastfeeding (P=0.000). There were significantly more formula-fed infants who were undernourished compared to exclusively-breastfed infants (14% vs. 8%, P=0.001). There were also significantly more infants in the formula-fed group who had abnormal head circumference compared to those in the exclusively-breastfed group (9% vs. 6%, P=0.031). Child development, as assessed by the Pre-screening Developmental Questionnaire, was similar between the two groups (P=0.996).Conclusion The overall rate of exclusive breastfeeding in Indonesia is 46.3%. Maternal unemployment is associated with longer duration of breastfeeding. Exclusive breastfed infants have significant better growth and head circumference compared toÂ formula fed infants, while the development is similar between the two groups.